Robot builder's bonanza - McComb, Gordon (New York : McGraw-Hill, 2011)
Presents instructions for more than one hundred robotic projects, describing useful tools, materials, and techniques, along with practical advice on power supply, robot locomotion, arm systems, circuit boards, microcontrollers, and remote control systems.
'TAB make great stuff!'--Cover.
Includes bibliographical references (p. 667-671) and index.
Keywords: Robotics